2019
DOI: 10.1016/j.injury.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with outcomes in traumatic cardiac arrest patients without prehospital return of spontaneous circulation

Abstract: In TCA patients transported to hospitals without prehospital ROSC, resuscitation attempts could be beneficial. We should aim to resuscitate patients as soon as possible with appropriate treatments for trauma patients, early activation of trauma team, and then, as a result, shorter resuscitation time will be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
2
11
1
1
Order By: Relevance
“…As expected an injury severity score (ISS<16) was associated with higher survival in traumatic arrest patients. This nding is in line with previous studies 5,13,16,25 and validates the need to incorporate ISS in outcome predictive models in not only trauma patients but also in traumatic arrests to avoid futility of extreme measures in resuscitation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As expected an injury severity score (ISS<16) was associated with higher survival in traumatic arrest patients. This nding is in line with previous studies 5,13,16,25 and validates the need to incorporate ISS in outcome predictive models in not only trauma patients but also in traumatic arrests to avoid futility of extreme measures in resuscitation.…”
Section: Discussionsupporting
confidence: 90%
“…This rate is slightly lower than the rate of 12.5% reported by Ahmed et al 5 but higher than other survival rates reported in earlier studies. 13,16 Young, white and male individuals continue to be mostly affected by traumatic arrests. 1,5,11 Improved survival in traumatic arrests presenting to U.S hospitals has been previously attributed to the increasing frequency of emergency interventions such as ED thoracotomy and other procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we compared the CPR and No-CPR groups in trauma patients who underwent REBOA within our study, no variables, except mortality and following treatment, showed significant differences between the two groups. Chen et al [11] reported that only 2.2% of traumatic cardiac arrest patients survived for at least 30 days, and ISS above 16 and total resuscitation length above 20 minutes were unfavorable factors for mortality. In our study, the mean ISS was 34.9±15.0.…”
Section: Discussionmentioning
confidence: 99%
“…Zu den Kriterien, die mit einem Überleben assoziiert sind, gehören das Vorhandensein einer Pupillenreaktion, Atembemühungen, Spontanbewegungen und ein organisierter EKG-Rhythmus [ 39 , 40 ]. Eine kurze Wiederbelebungsdauer, kurze präklinische Zeiten [ 41 ], ein penetrierendes Thoraxtrauma [ 42 ], ein beobachteter Kreislaufstillstand und das Vorhandensein eines defibrillierbaren Rhythmus sind ebenfalls mit guten Ergebnissen verbunden [ 43 , 44 ]. Kinder, bei denen es zu einem TCA kommt, zeigen ein besseres Überleben als Erwachsene [ 28 , 29 ].…”
Section: Evidenz Die In Die Leitlinien Einfließtunclassified